2017
DOI: 10.1111/1462-2920.13618
|View full text |Cite
|
Sign up to set email alerts
|

Shared and host‐specific microbiome diversity and functioning of grapevine and accompanying weed plants

Abstract: Weeds and crop plants select their microbiota from the same pool of soil microorganisms, however, the ecology of weed microbiomes is poorly understood. We analysed the microbiomes associated with roots and rhizospheres of grapevine and four weed species (Lamium amplexicaule L., Veronica arvensis L., Lepidium draba L. and Stellaria media L.) growing in proximity in the same vineyard using 16S rRNA gene sequencing. We also isolated and characterized 500 rhizobacteria and root endophytes from L. draba and grapevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
55
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(70 citation statements)
references
References 96 publications
12
55
3
Order By: Relevance
“…In addition, the bacterial community structures were markedly different (p < 0.05) in the BS, RZS, RS, and TS samples between non-stony and stony soils, but there was no signi cant difference (p > 0.05) within the same soil type, based on the ANOSIM analysis (Table 2), further indicating that the soil microbiota induced by stony soils largely changed the microbiota of RS and TS in T. hemsleyanum. This was consistent with the observation that soil type was a major driver of microbiota in the root environment [34].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the bacterial community structures were markedly different (p < 0.05) in the BS, RZS, RS, and TS samples between non-stony and stony soils, but there was no signi cant difference (p > 0.05) within the same soil type, based on the ANOSIM analysis (Table 2), further indicating that the soil microbiota induced by stony soils largely changed the microbiota of RS and TS in T. hemsleyanum. This was consistent with the observation that soil type was a major driver of microbiota in the root environment [34].…”
Section: Discussionsupporting
confidence: 92%
“…Our results demonstrated that the soil and rhizosphere associated with Dioon coralloid roots are highly diverse. As with other plants [25,66,67], the soil (bulk soil and rhizosphere) is more diverse in the number of OTUs and genera than the root endosphere, although these differences are not significant in our study (alpha diversity metrics). When we compared the rhizosphere and endosphere from the six Dioon samples (set 3 comparison), we found significant differences in the alpha diversity, with higher diversity on the outside than the inside of coralloid root, a common pattern reported previously in 30 species of angiosperms [68].…”
Section: A Taxonomically Diverse Bacterial Community Inside Dioon Corcontrasting
confidence: 56%
“…NGS-based metagenomics is now contributing to deeper insights into the plant microbiome associations and interactions (Lebeis 2015, Samad et al 2017). Tissue culture system provided a good tool to study the microbial endophytes protected from environmental organisms.…”
Section: Discussionmentioning
confidence: 99%